(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Sex identification in Heterotis niloticus based on morphometric and meristic structures was carried out in Maiduguri with the aim of sex differentiating in Heterotis niloticus using morphological structure. Twenty (20) adults males and females Heterotis niloticus were randomly collected from Alau lake and convey to fish hatchery complex of department of fisheries university of maiduguri. The weight and length of each specimen were taken using a top-loading weighing balance and a meter rule. Morphomotric measurements such as ratio of dorsal fin length, pre-dorsal fin length, head length, peduncle length, anal fin length, pectoral fin length, pelvic fin length, caudal fin length, the standard length were measured while the meristic characters counted include the number of lateral lines, sensory pits, number of genital openings, number of anal, pelvic, dorsal, caudal and scales above the lateral line. The data obtained from the experiment were subjected to descriptive and inferential analysis using statistix 8.0 as a package. The result shows that, both the morphometric and meristic characters were the same for both sexes. However, the presence of small papillae on a loop separating the two opening in the male differentiates the male from the female. Therefore, meristic features can be used to identify male Heterotis niloticus fish especially during selection for breeding